USO DO INSTAGRAM, SATISFAÇÃO DA IMAGEM CORPORAL E AUTOESTIMA EM MULHERES JOVENS - Pires Portugal, Mariana (2022)
The aim was to assess the impact of Instagram's usage on young women's satisfaction with their body image and self-esteem. This is a quantitative cross-sectional study. A total of 329 women using Instagram, aged 18-24, answered this online survey. The data collection was through the RedCap platform. The research was published on social networks and was requested that other people would share on theirs. The method used was a non-probabilistic sample in order to reach as many participants as possible. The results showed that those who reported access to inspirational fitness content most frequently and compared themselves to other users showed decreased body satisfaction and self-esteem. Those who spend more than 2 hours per day on Instagram increased subjective feelings of salience and body fat perception. Time spent on Instagram increased the number of followers related to more self-esteem, strength, and physical fitness. Time spent, the frequency of Instagram use, and the type of content that women interact with, may relate to worse subjective feelings of self-esteem, salience, perception of body fat, disparagement and attractiveness.